2004
DOI: 10.1001/archneur.61.6.865
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Homocysteine Level in Patients With Parkinson Disease

Abstract: Background: An elevated plasma homocysteine (Hcy) level has been prospectively associated with an increased risk of vascular and degenerative dementias. An Hcy elevation is prevalent in patients with Parkinson disease (PD) in part because levodopa metabolism produces Hcy. The clinical relevance of an elevated Hcy level in patients with PD is unknown.Objective: To determine if hyperhomocysteinemia in patients with PD is associated with depression or with cognitive or physical impairments.Design: Ninety-seven pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
99
3
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 31 publications
(34 reference statements)
13
99
3
2
Order By: Relevance
“…Only 1/4 studies reported a significant association between the presence of VRF and a decline in the construction praxis. O'Suilleabhain et al (2004; found a significantly worse performance on Block Design (WAIS-III) and on ROCF-copy in the PD group with Hcy>14 μmol/L compared to PD with Hcy < 14 μmol/L at baseline, but not at 2-year follow-up.…”
Section: Construction Praxismentioning
confidence: 78%
See 4 more Smart Citations
“…Only 1/4 studies reported a significant association between the presence of VRF and a decline in the construction praxis. O'Suilleabhain et al (2004; found a significantly worse performance on Block Design (WAIS-III) and on ROCF-copy in the PD group with Hcy>14 μmol/L compared to PD with Hcy < 14 μmol/L at baseline, but not at 2-year follow-up.…”
Section: Construction Praxismentioning
confidence: 78%
“…Six studies (Barone et al, 2008-at baseline only); Camicioli et al, 2009;Hassin-Baer et al, 2006;O'Suilleabhain et al, 2004O'Suilleabhain et al, , 2006Ozer et al, 2006;Rodriguez-Oroz et al, 2009) found no association between Hcy and worse global cognition as measured by the MMSE (n=5 studies), the ADAS-Cog (n=1), the BDS (n=1), the DRS (n=1) and the STMS (n=1 study). However, the R-DB-PC study of Barone et al (2008) found that Hcy-rivastigmine-treated patients significantly improved their performance after 24 weeks on the ADAS-Cog and the MMSE compared to Hcy-placebo-treated-patients.…”
Section: Association Between Vrf and A Score Of Global Cognitionmentioning
confidence: 96%
See 3 more Smart Citations